Father Luis Olivares, a Biography : Faith Politics and the Origins of the Sanctuary Movement in Los Angeles - García, Mario T. (Book collections on Project MUSE., 2018)
"This is the amazing untold story of the Los Angeles sanctuary movement's champion, Father Luis Olivares (1934-1993), a Catholic priest and a charismatic, faith-driven leader for social justice. Based on previously unexplored archives and over ninety oral histories, this compelling biography traces the life of a complex and constantly evolving individual, from Olivares's humble beginnings in San Antonio, Texas, to his close friendship with legendary civil rights leader Cesar Chávez and his historic leadership of the United Neighborhoods Organization and the sanctuary movement"--